Study of biocompatibility effect of nanocarbon particles on various cell types in vitro: Untersuchungen zur Biokompatibilität von Kohlenstoff‐Nanoröhren auf verschiedenen Zelltypen in vitro. Issue 2 (1st February 2016) - Tolkachov, M.; Sokolova, V.; Loza, K.; Korolovych, V.; Prylutskyy, Y.; Epple, M.; Ritter, U.; Scharff, P.
Abstract : The viability of primary cells (human mesenchymal stem cells, hMSC, as a model for healthy cells) and a cancer cell line (human transformed cervix epithelial cells, HeLa, as a model for cancer cells) was studied with the MTT assay after the incubation with water‐soluble C60 fullerenes and multi‐walled carbon nanotubes filled by iron, respectively. The size of the particles was determined by dynamic light scattering. The morphology of the cells incubated with nanocarbon particles was studied by scanning electron microscopy. The effect of C60 fullerenes and Fe‐multi‐walled carbon nanotubes on the cells is depending on the concentration of applied nanoparticles.